2021
DOI: 10.3389/fvets.2021.611153
|View full text |Cite
|
Sign up to set email alerts
|

Are Marbling and the Prediction of Beef Eating Quality Affected by Different Grading Sites?

Abstract: For the European abattoirs, the preferred carcass grading site is at the fifth rib, and cutting at the tenth rib as in Australia could lead to a lower economic value of the carcass. Therefore, the objective of this study was to compare the grading scores of marbling and the meat and fat color on Musculus longissimus thoracis et lumborum (LTL) at the fifth and the tenth thoracic vertebrae. The consequences on the prediction of beef eating quality using the Meat Standards Australia (MSA) grading scheme were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Recently, carcass grading with marbling assessment was conducted in a French private meat plant. This study found no significant difference in marbling score between the 5th and 10th ribs, such that marbling score could be measured at the quarter carcass level [ 175 ]. This could provide a theoretical basis for the introduction of marbling score in the European carcass grading system.…”
Section: Main Methods For Measuring and Predicting Beef Qualitymentioning
confidence: 99%
“…Recently, carcass grading with marbling assessment was conducted in a French private meat plant. This study found no significant difference in marbling score between the 5th and 10th ribs, such that marbling score could be measured at the quarter carcass level [ 175 ]. This could provide a theoretical basis for the introduction of marbling score in the European carcass grading system.…”
Section: Main Methods For Measuring and Predicting Beef Qualitymentioning
confidence: 99%
“…When measured at the 10th rib site, at 72 h post-mortem, there was no difference in L* value after 1 h or 24 h of exposure to air. This suggestion of an interaction between lightness and site of measurement may be due to variation in colour along the longissimus thoracis et lumborum muscle as described in [ 25 ] and possibly, the different susceptibilities at different positions of the LT to changes in the pre-slaughter management of the bulls. While it is recognised that comparison of the two locations is confounded by the methodology used and the timing of measurement, simultaneous assessment of treatment effects on lightness at several locations/muscles merit consideration, particularly from a commercial perspective.…”
Section: Discussionmentioning
confidence: 97%
“…In general, IMF highly contributes to beef eating quality with strong correlations (r = 0.74 to 0.88, p < 0.05) between IMF content and tenderness, juiciness, flavor liking, and overall liking being reported [ 44 ]. The contribution of marbling score to the variability in MQ4 score is up to 51% for m. longissimus thoracis et lumborum [ 45 ]. However, in the present study, no significant correlation was found between marbling score and eating quality scores assessed by both consumers and panelists.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, given that the current animals were young and lean, specific relationships might exist between animal and muscle characteristics and eating quality traits. Indeed, beef eating quality is multifactorial determined, for instance, with various effects of marbling depending on muscle cut [ 45 ] or with a low effect of breed on eating quality [ 48 ].…”
Section: Discussionmentioning
confidence: 99%